Influence of potential induced degradation phenomena on electrical insulating backsheet in photovoltaic modules - Zhang, Jia-Wei; Song, Chen (Journal of cleaner production, 2019)
Because of improving solar-cell fabrication and converter technology, solar photovoltaic (PV) systems have emerged as one of the most promising methods of renewable power generation. In PV modules, polyethylene terephthalate (PET) is usually used as a backsheet to provide electrical insulation and physical protection. However, such backsheets have various problems, including potential induced degradation from partial discharge (PD), which affect the service life of the PV system. In this study, the PD discharging characteristics of PET film and its degradation of insulation structure caused by the PD are analyzed and compared. The PET was pretreated and electrically stressed above the PD inception voltage (PDIV) for 10, 30, 60, and 120min. Using phase-resolved partial discharge (PRPD), we found that the discharge magnitude changed with differing discharge time. In addition, using differential scanning calorimetry (DSC), we found that the crystallinity of the PET increased with aging time. This paper presents a comprehensive study of the electrical degradation of the backsheet, using PRPD patterns and changes in crystallinity, which will help to improve the long-term service life of PV systems.